Situações desencadeadoras de aprendizagem de área na EJA na perspectiva da Teoria Histórico-Cultural com o uso de tecnologias digitais - Borba, Bruno Tizzo (2023)
This research focused on studying possible didactic and social contributions in the process of appropriating the concept of area when using digital technologies in a Triggering Learning Situation (Situação Desencadeadora de Aprendizagem - SDA), in Adult and Youth Education (Educação de Jovens e Adultos - EJA). The study was grounded in Activity Theory and supported by the theoretical-methodological assumptions of Teaching Guided Activity. The general objective was to analyze didactic and social possibilities of the Triggering Learning Situation developed with the aid of Digital Technologies for teaching and learning the concept of area with EJA students. The specific objectives were: to analyze the didactic possibilities of the SDA with the use of digital technologies in the process of appropriating new meanings related to the concept of area in EJA, and to investigate the social potential of Digital Technology in the development of an SDA in the teaching and learning process of the concept of area within the scope of EJA. The actions and reflections were guided by the following research question: what didactic and social possibilities can the development of the SDA with digital technological resources offer for teaching and learning the concept of area with EJA students? The research was conducted with sixth and seventh-grade classes of the Adult and Youth Education (EJA/Proeja) at the School of Basic Education of the Federal University of Uberlândia (Eseba-UFU). To achieve the objective and answer the research question, the logical-historical movement of the concept of area was studied, understanding them as human production and addressing essential mathematical relations of these teaching objects in historical records of humanity. An SDA, characterized as a virtual story of the concept, was developed, relying on the conceptual connections evidenced in the logical-historical movement of the concept of area for the sixth and seventh grades of EJA. Through the analyses conducted, it was evident that the students, when using digital technologies in an SDA, appropriated the concept of area through interaction with their peers and/or the teacher-researcher, and were able to attribute new meanings to the concepts worked on during the development of the proposal. Moreover, didactic and social contributions were observed by providing conditions for the students to engage in learning activities, appropriate mathematical and technological knowledge, as well as promoting digital and social inclusion for these EJA students.